Increased efficacy of dietary supplement containing wax ester-rich marine oil and xanthophylls in a mouse model of dry macular degeneration - Melecchi, Alberto; Amato, Rosario; Lapi, Dominga; Dal Monte, Massimo; Rusciano, Dario; Bagnoli, Paola; Cammalleri, Maurizio (Frontiers in Pharmacology, 2022)
Age-related macular degeneration (AMD) is nowadays considered among the retinal diseases whose clinical management lacks established treatment approaches, mainly for its atrophic (dry) form. In this respect, the use of dietary patterns enriched in omega-3 and antioxidant xanthophylls has emerged as a promising approach to counteract dry AMD progression although the prophylactic potential of omega-3 of fish origin has been discussed. Whether enriched availability of omega-3 and xanthophylls may increase the effectiveness of diet supplementation in preventing dry AMD remains to be fully established. The present study aims at comparing the efficacy of an existing orally administered formulation based on lutein and fish oil, as a source of omega-3, with a novel formulation providing the combination of lutein and astaxanthin with Calanus oil (COil), which contains omega-3 together with their precursors policosanols. Using a mouse model of dry AMD based on subretinal injection of polyethylene glycol (PEG)-400, we assessed the comparative efficacy of both formulations on PEG-induced major hallmarks including oxidative stress, inflammation, glial reactivity and outer retinal thickness. Dietary supplementation with both mixtures has been found to exert a significant antioxidant and anti-inflammatory activity as reflected by the overall amelioration of the PEG-induced pathological hallmarks. Noteworthy, the formulation based on COil appeared to be more protective than the one based on fish oil, presumably because of the higher bioavailability of omega-3 in COil. These results support the use of dietary supplements combining omega-3 and xanthophylls in the prevention and treatment of AMD and suggest that the source of omega-3 might contribute to treatment efficacy.